Body size traits in the flightless bush-cricket are plastic rather than locally adapted along an elevational gradient - Jarčuška, Benjamín; Krištín, Anton; Kaňuch, Peter (Evolutionary ecology, 2023)
Elevational gradients are closely associated with strong abiotic variation at small spatial scales and provide a powerful tool to assess species’ adjustments to climatic and other environmental factors. To understand the role of genetic underpinning and environmentally-induced plasticity on body size, we compared variation in a range of morphological traits in wild-caught and lab-reared (F1 generation) dark bush-crickets ( Pholidoptera griseoaptera ) from 10 populations sampled along an elevational gradient of approximately 1100 m. We used linear mixed models (LMM) and linear models to test the effects of sex, rearing environment (wild-caught vs. lab-reared), elevation and population identity, and the interactions between these factors on trait variation. In LMM, population identity was used as a random effect to test for trait inter-population repeatability. In the lab, we found genetically-based differences between populations; however, this variation wasn’t elevation-dependent, suggesting that it’s not locally adapted to elevation and associated environmental variables. In contrast, we observed a weak negative association between elevation and locomotor traits (hind femur length and hind tibia length), pronotum width and females’ ovipositor length in wild-caught bush-crickets, which could be attributable to environmentally-induced phenotypic plasticity. Plasticity could also be responsible for lower differences between populations and lower repeatability within populations in the wild than in the lab environment, and larger body-size traits in wild-caught bush-crickets. The lower repeatability in wild populations can be explained by the greater temporal and spatial environmental heterogeneity in the wild compared to lab. Sex-specific morphological differences were more pronounced in the wild than in the laboratory. Since we can assume limited gene flow between populations of the species, we can conclude that other fitness-related traits are subject to selection and thus enable the broad elevational distribution of this bush-cricket.